Design and modeling of solar parabolic trough power plant with MATLAB - Mohammad, S.T. (EDP Sciences, 2017)
With the fact that Malaysia is one of the fast- growing countries, demand of energy increment is rapid. Malaysia is able to obtain ample amount of annual solar radiation due to its location at equator. If this is utilized proficiently and effectively, then, it can suffice the domestic needs as well as the industrial needs in terms of energy consumption. This article proposes a parabolic Trough Power Plant which is designed with 1.2 kW net electric output. Consequently, the results of theoretical calculations are detailed in the article, while, ensuring the analysing of design proposed through the MATLAB software. The results showed that by making use of aperture having an area of approximately 80 m2, maximum useful heat gain of 20701W at 13:00 pm was attained in March. The maximum net power is 11.84 kWh/day in February. © The authors, published by EDP Sciences, 2017.